MicroRNA-mediated susceptible poplar gene expression regulation associated with the infection of virulent Melampsora larici-populina. (December 2016) - Li, Danlei; Wang, Feng; Wang, Chao; Zou, Li; Wang, Zhiying; Chen, Qiaoli; Niu, Chunyang; Zhang, Ruizhi; Ling, Yaming; Wang, Bowen
Abstract Background Rust caused byMelampsora larici-populina is one of the most damaging diseases of poplars. Rust is considered to be a model pathogen for genetic studies because both pathogen and host genomes are available. The poplar 'Robusta', whose general rust resistance is defeated by virulent rust E4, provides suitable host material for studies of the gene regulation involved in rust resistance/susceptibility. In this study, we investigated the microRNA-mediated susceptible poplar gene expression regulation associated with the infection of virulent rust. We were particularly interested in delineating the host-pathogen interactions with a specific focus on microRNAs (miRNAs). Results To study the susceptibility of poplar toM. larici-populina, small RNA (sRNA) libraries, a degradome cDNA library and digital gene expression libraries were constructed for rust-inoculated and rust-free susceptible poplar 'Robusta' leaves through high-throughput sequencing. Altogether, 12, 722 regulating interactions were identified. The results delineated the framework of post-transcriptional regulation of gene expression in the susceptible poplar, which was infected by the virulent rust. The results indicated that pathogen-associated molecular patterns (PAMPs) and PAMP-triggered immunity were induced by the infection of virulent rust E4 and that miRNAs still functioned at this stage. After this stage, miRNA-regulatedR genes, such as TIR-NBS-LRR and CC-NBS-LRR, were not fully functional. Additionally, the rust-responsive miRNAs did not regulate the signaling component genes related to the salicylic acid pathway or the hypersensitive response. Conclusions We found that the defense-related post-transcriptional regulation of the susceptible poplar 'Robusta' functions normally only at the stage of PAMPs and PAMP-triggered immunity (PTI). More importantly, the miRNA-mediated post-transcriptional regulation of defense signal pathway genes were inactivated by the infection of virulent rust at the stage of effector-triggered susceptibility and during the following stages of salicylic acid and hypersensitive responses. This inactivation was the major characteristic of 'Robusta' susceptibility.